Study the Radiological Assessment for Italian Radioisotops Production Laboratory (IPRL) (Tuwaitha-Iraq) - Kitah, Fouzey H; Al-Bahkat, Yousif M Zayir; Mahdi, Assim A; Sakran, Amer A (Al-Nahrain Journal of Science, 2013)
In order to study assessment of the annual doses and cancer risk lifetime related in IRPL laboratory, the field measurements were performed on a systematic grid .Soil samples were collected and prepared for laboratory analyzed by using gamma spectrometry system (HPGe). RESRAD software version (6.5) was used to assess the annual doses and probability of excess cancer risk lifetime incurred by workers exposed to radioactive material. The results indicated that the Total Effected Dose Equivalent (TEDE) received from artificial radionuclides IP-139, IP-79, and IP-184 are (2.116, 0.394, 10.97) mSv/y respectively are exceed the regulatory dose limit adopt by NRC (Nuclear Regulatory Commission) (0.25mSv/y) and (0.3mSv/y) of IAEA criteria, while TEDE from natural radionuclides sample (IP-15) is (0.03459mSv/y) less than the basic dose limit. The artificial radionuclides cells must be treated to keep IRPL, workers and surrounding environment within accepted limit.